Inovasi Strategis Industri Kreatif Digital Berbasis Start-up dalam Meningkatkan Keunggulan Bersaing di Era Industri 4.0 - Syaifudin , Muhammad; Nuruddin, Nuruddin; Nur Fauzi, M. Asif (Institut Agama Islam YPBWI Surabaya, 2025)
This study aims to examine the role of strategic innovation in driving competitive advantage in the digital creative industry in the Industrial Revolution 4.0 era. Rapid technological developments have changed the competitive landscape, requiring industry players to be able to adapt through innovative strategies that focus not only on products, but also on processes, business models, and customer experiences. This study uses a qualitative approach with a case study method on several digital creative industry players in Indonesia. Data were collected through in-depth interviews, observations, and documentation, then analyzed thematically. The results of the study indicate that strategic innovation that includes the use of digital technology, cross-sector collaboration, and data-based and creativity approaches can increase competitiveness and maintain business relevance amid disruption. This study emphasizes the importance of adaptive capabilities and a culture of innovation in responding to the challenges of the Industrial Revolution 4.0 era. These findings provide theoretical contributions to the development of business strategies in the creative sector as well as practical implications for industry players to formulate sustainable innovation policies.